Restorative Justice Tindak Pidana “Elopement” Hukum Adat dalam Konstruksi Hukum Pidana Positif Indonesia - Sri Wahyu Kridasakti; Abd. Majid; Henny Yuningsih (Universitas Islam Balitar, Blitar, 2022)
This study examines the applicability of “elopement” customary law (“elopement”) in the construction of criminal law in Indonesia. This legal-system study uses a socio-legal methodology with the research locus in Mataram Marga Village, Sukadana District, East Lampung; Sade Village, Central Lombok, NTB; and Tenganan Karangasem Bali, with three findings. First, customary law (legal-culture) in determining the meaning and meaning of adult (legal and legitimate) is different from the meaning of adult according to positive law (Civil Code, Criminal Code and Law 1/1974). Second, the legal-structure of positive criminal law is superior to customary law or living-law (tradition) in the construction of restorative-justice through